ADHD-Related Neurodiversity and the Entrepreneurial Mindset. (January 2021) - Moore, Curt B.; McIntyre, Nancy H.; Lanivich, Stephen E.
To better understand how neurodiversity (i.e., neurobiological/brain-related differences) is related to entrepreneurial cognition, this study draws on prior research from entrepreneurship and neuroscience to empirically examine the relationship between attention-deficit/hyperactivity disorder (ADHD) and the entrepreneurial mindset. We examine differences between entrepreneurs with and without ADHD in cognitive style, entrepreneurial alertness, metacognition, and resource-induced coping heuristic (RICH). Our results suggest neurodiversity from ADHD is meaningfully related to aspects of an entrepreneurial mindset. Our results suggest entrepreneurs with ADHD employ a more intuitive cognitive style and demonstrate higher levels of entrepreneurial alertness and RICH, while no significant differences in metacognition were found.